Gall stone ileus: An uncommon cause of small bowel obstruction at an unusual age: A Case report (Nepal Medical College Journal, 2022)
Gallstone ileus is a rare complication of cholelithiasis. It is an uncommon cause of a mechanical small bowel obstruction. Repeated episodes of cholecystitis results adhesion of the gallbladder to the small bowel (usually duodenum) with eventual formation of cholecystoenteric fistula via which gallbladder stone enters the small bowel. It is most commonly seen in elderly females hence linked with high morbidity & mortality. Computed tomography (CT) imaging have made it easier to diagnose gallstone ileus effectively. Surgical intervention results in prompt relief of obstructive symptoms by removing stone & repairing fistula. Here is a case of gall stone ileus in a 27-year-young gentleman who presented to us with history of acute abdomen & without any comorbidities or biliary manifestation.